Molecular detection of genetic defects in ambiguous genitalia (AG) and congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency - Zain, Fuziah Md; Isa, Mohd Nizam; Awang, Rus Anida (2000)
Congenital adrenal hyperplasia (CAH) is a group of inherited disorders affecting the enzymes catalyzing the synthesis of steroids in the adrenal cortex.Malfunction of 21-hydroxylase is the most frequent defect among these disorders.This enzyme is essential for the synthesis of cortisol and aldosterone.The decreased level of serum cortisol in patients with 21-hydroxylase cleticiency stimulates ACTH secretion, which result in elevated levels of steroid precursors as 17-hydroxyprogesterone and increased production of adrenal androgens causing virilization.Deficiency of the 2 I -hydroxylase (21-0H) enzyme is by far the most common form of CA H which arises as a result of deletions or deleterious mutations in the active gene (CYP21) located on chromosome 6p21.3.Many different mutations of the CY P21 gene cause varying degrees or impairment of 21-0H activity that results in a spectrum of disease statement.There is no sharp limit between the salt-wasting, the simple virilizing and the late onset forms.The objective of our study was to determine the 21-0H deticiency mutation defects and correlate the genotype with their phenotypic statement of the disease.vVe performed mutational analysis using Polymerase Chain Reaction-Allele Specific Oligonucleotide Hybridization (PCR-ASOH) technique on patients who were suspected to have CAH as they presented with ambiguous genitalia (AG) and or electrolyte derangement.Among the 52 patients, 3 had Val281 Leu mutation (5.76%). 2 had Pro30Leu mutation (3.85%). I had Gln318stnp mutation (1.92%) and in 46 (88.l6%) patients mutation was detected.The three patients with Val281 Leu mutation had presented with adrenal crises during in infancy and was classified as salt losers and treated with glucocorticoids and mineralocorticoids.These 3 patients could well be the other 40% who are categorized as salt-losers. The two patients with Pro30Leu mutations have normal male external genitalia and presented with hyponatraemia and hyperkalaemia.Only one patients required mineralocorticoid therapy that was given for about 5 months duration.Subsequently he hold normal electrolytes level even without mineralacorticiod therapy. The Gln3I8stop mutation was identitied in one patient who presented with ambiguous and adrenal crises.Our study showed that the cases with genotype Val281 Leu, Pro30Leu and Gln318stop mutations correlated with their phenotype. The mutation analysis of CYP21 gene proved to be a good complementary investigation and supportive to the diagnosis and management of our CAH patients.